Targeted delivery system for cancer cells consist of multiple ligands conjugated genetically modified CCMV capsid on doxorubicin GNPs complex - Barwal, Indu (Sci Rep, 2016)
Targeted nano-delivery vehicles were developed from genetically modified Cowpea chlorotic mottle virus (CCMV) capsid by ligands bioconjugation for efficient drug delivery in cancer cells. RNA binding (N 1-25aa) and β-hexamer forming (N 27-41aa) domain of capsid was selectively deleted by genetic engineering to achieve the efficient in vitro assembly without natural cargo. Two variants of capsids were generated by truncating 41 and 26 amino acid from N terminus (NΔ41 and NΔ26) designated as F(1) and F(2) respectively. These capsid were optimally self-assembled in 1:2 molar ratio (F(1):F(2)) to form a monodisperse nano-scaffold of size 28 nm along with chemically conjugated modalities for visualization (fluorescent dye), targeting (folic acid, FA) and anticancer drug (doxorubicin). The cavity of the nano-scaffold was packed with doxorubicin conjugated gold nanoparticles (10 nm) to enhance the stability, drug loading and sustained release of drug. The chimeric system was stable at pH range of 4–8. This chimeric nano-scaffold system showed highly specific receptor mediated internalization (targeting) and ~300% more cytotoxicity (with respect to FA(−) delivery system) to folate receptor positive Michigan Cancer Foundation-7 (MCF7) cell lines. The present system may offer a programmable nano-scaffold based platform for developing chemotherapeutics for cancer.